OIL PRICE FLUCTUATIONS AND THEIR IMPACT ON THE ECONOMIC INDICATOR OF SUSTAINABLE DEVELOPMENT REPRESENTED BY THE GROSS DOMESTIC PRODUCT IN IRAQ FOR THE PERIOD 2010-2023 (World Economics and Finance Bulletin, 2026)
The funds made from crude oil so important for the financial resources of Iraq that it has become the chief financing source of development projects in the general budget. The study that we have if, however, it finds a co-integration relation between two variables, that is the oil prices and the GDP, will achieve the aims set above. Investigating causality between oil prices and GDP through the directionality of the analysis. That is to say, the economic review. The recent shift in oil prices influenced GDP, which is one of the sustainable development indicators, and it was looked into. There was a positive short-run link between oil prices and GDP. For instance, a $1 rise in oil prices will result in a $10 rise in GDP. The study finds the opposite according to this data. Put differently, for every dollar oil price increases GDP will fall by a dollar 1.8. Utilization of oil revenues should take place as soon as possible. For a long time, the foreign monopolistic firms’ control or wars and economic sanctions hardly gave rise to the application of revenue in the competitive market. They were squandered because of corruption over in Iraq, on the other hand. A rise in crude oil prices will create new regime and opportunities for growth in type of GDP and a production increase in the long term.
Keywords: Oil prices; GDP